Status of neurosonology in Spain. A study from the Spanish Society of Neurosonology (SONES) - J. Rodríguez-Pardo; J. Carneado-Ruiz; M. Martínez-Martínez; J.M. Moltó-Jordá; P. Irimia; J. Serena-Leal; Ó. Ayo-Martín; P. Martínez-Sánchez; J. Pagola; J. Fernández-Domínguez (Neurología (English Edition))
Introduction: Neurosonology is the field of study of the ultrasound techniques applied to neurological diseases. The Spanish Society of Neurosonology (SONES) was funded in 1997 to promote training and education in these techniques, especially focused on the study of cerebrovascular diseases. After 25 years, the increased use of other advanced neurovascular imaging techniques and the emergence of novel applications of ultrasound in other fields of neurology, have modified the classic role of neurosonology. From the SONES we aimed to evaluate the current status of neurosonology in Spain. Methods: Cross-sectional survey of neurologists and neurology residents working in Spain regarding training, education, and local daily practice, including a strengths, weaknesses, opportunities and threats (SWOT) analysis. Results: One-hundred seventy-eight neurologists and thirty-four neurology residents participated in the survey. A wide experience in vascular neurosonology (90% of respondents’ Neurology departments) and limited experience in brain parenchyma sonography (34%), cardiac echoscopy (25%), ultrasound-guided techniques (24%), and nerve ultrasound (14%) was reported. Fifty-three percent of the participants reported to have a full-time neurosonology lab in their department and only 14% reported to have neurologists dedicated exclusively to neurosonology. Most participants (54%) reported to lack continuous learning opportunities, and 97% to need training in one or more neurosonology techniques. Main SWOT were respectively requiring expertise, shortage of time, versatility and comprehensive management of the neurological patient. Conclusion: Vascular neurosonology is widely instituted in Spain, but the implementation of full-time neurosonology labs and training in non-vascular neurosonology techniques is yet scarce. Resumen: Introducción: La neurosonología es la disciplina que estudia las técnicas ultrasonográficas aplicadas a la neurología. En 1997 se fundó la Sociedad Española de Neurosonología (SONES) con el objetivo de promover la formación de neurólogos en estas técnicas, especialmente en el campo de las enfermedades cerebrovasculares. Veinticinco años después, la generalización de otras técnicas más avanzadas de neuroimagen vascular, y el desarrollo de la ultrasonografía en otros campos de la neurología, han modificado el papel que clásicamente se ha atribuido a esta disciplina. Desde la SONES analizamos el estado actual de la neurosonología en España. Métodos: Estudio transversal mediante una encuesta en línea dirigida a residentes de neurología y neurólogos ejercientes en España, abordando cuestiones de formación y práctica diaria, incluyendo un análisis de debilidades, amenazas, fortalezas y oportunidades (DAFO). Resultados: Participaron 178 neurólogos y 34 residentes. Reflejaron una amplia experiencia en neurosonología vascular (90% de los Servicios) y escasa en parénquima cerebral (34%), ecocardioscopia (25%), técnicas ecoguiadas (24%), y ecografía de nervio (14%). El 53% afirmó disponer de un laboratorio de Neurosonología a tiempo completo y solo el 14% de facultativos dedicados en exclusiva a la neurosonología. La mayoría afirmó que la formación continuada en neurosonología es escasa, y el 97% creen necesario potenciar alguna de las técnicas. Las principales DAFO fueron respectivamente la necesidad de experiencia, la falta de tiempo, la versatilidad y el manejo integral del paciente neurológico. Conclusiones: La neurosonología vascular está ampliamente implantada en España, pero la implementación de laboratorios dedicados y formación en técnicas no vasculares es aún escasa.